(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Emesis Gravidarum is a common symptom in pregnancy and occurs in 50-60% of pregnant women. In addition to consuming drugs to treat nausea and vomiting, mothers can try the recommended fruits such as bananas which can overcome Emesis Gravidarum. In bananas it contains Vitamin B which is soluble in water and helps increase the development of central nervous system cells in the fetus. A preliminary survey conducted at the Sidomulyo Inpatient Health Center in Pekanbaru City showed that 8 out of 10 pregnant women experience Emesis Gravidarum so that it can cause discomfort for pregnant women. The purpose of this study was to effect of ambon banana on Emesis Gravidarum in pregnant women at Sidomulyo Inpatient Health Center, Pekanbaru City in 2019. This type of research is a pre-experiment with one group pre-post test design. This research was conducted from March to June 2019. The population in this study were all pregnant women who experienced Emesis Gravidarum with a sample of 19 people taken by accidental sampling technique. The results showed that the average score of nausea vomiting with mothers Emesis Gravidarum before given ambon banana was 10,21 (SD=2,175) and after being given ambon banana was 7,21 (SD=2,200). The result of the Wilcoxon test statistical test showed that there was an effect of giving ambon banana to Emesis Gravidarum in pregnant women with (p-value 0,000). It is recommended for midwives to provide education about ambon banana as one of the nutrients from natural ingredients to reduce Emesis Gravidarum during pregnancy.